2022
DOI: 10.3389/fenvs.2022.1025756
|View full text |Cite
|
Sign up to set email alerts
|

Oil rents, economic growth, and CO2 emissions in 13 OPEC member economies: Asymmetry analyses

Abstract: Oil rents significantly contribute to income in OPEC member economies and could have environmental consequences. The present study explores the asymmetrical effects of oil rents on CO2 emissions in 13 current OPEC economies using a period 1970–2019, and also tests the Environmental Kuznets Curve (EKC) hypothesis. Long-run results show that economic growth has a positive effect, and its square term has a negative effect on CO2 emissions in Algeria, Congo, Gabon, Kuwait, and Saudi Arabia, which validate the EKC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…The literature implies that using renewable energy sources can help safeguard the environment, whereas using non-renewable ones can lead to a decline in ecological performance (Mahmood and Saqib, 2022;Khan et al, 2022b). This standpoint is confirmed by a number of empirical studies, including those conducted by (Saqib et al, 2022a) for the MINT nations, (Saqib et al, 2022b) for GCC countries, and (Sharif et al, 2022;Saqib et al, 2022e) for the E7 and G7 countries.…”
Section: Review Literaturementioning
confidence: 87%
“…The literature implies that using renewable energy sources can help safeguard the environment, whereas using non-renewable ones can lead to a decline in ecological performance (Mahmood and Saqib, 2022;Khan et al, 2022b). This standpoint is confirmed by a number of empirical studies, including those conducted by (Saqib et al, 2022a) for the MINT nations, (Saqib et al, 2022b) for GCC countries, and (Sharif et al, 2022;Saqib et al, 2022e) for the E7 and G7 countries.…”
Section: Review Literaturementioning
confidence: 87%
“…Utilizing the panel vector error correction model [ 53 ], found that while there is no long-term causal link between renewable energy consumption and CO 2 emissions, there is a short-term association running in the opposite direction, from renewable energy to CO 2 emissions. As a result, while renewable energy and carbon dioxide emissions are independent in the long run, carbon dioxide emissions are dependent on renewable energy in the short run [ 54 , 55 ]. Since more people are becoming aware of how important it is to look at energy sources in terms of emissions, there has been a significant development in the literature to capture emissions from energy sources.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In further explaining this notion, Badeeb et al (2020) argued that oil rent positively influences the CO 2 emission. It significantly adds to the country's GDP, thus bringing adverse environmental consequences (Mahmood & Saqib, 2022).…”
Section: Introductionmentioning
confidence: 99%